Social Epidemiology Analysis of Overweight in Toodler at Sukagumiwang Public Health Center Indramayu District (KEMAS: Jurnal Kesehatan Masyarakat, 2018)
The prevalence of obesity in children has increased from year to year. Patterns and eating behaviors, lack of physical activity and heredity are considered factors causing overweight.The purpose of this study to analyze the social epidemiology of overweight incidence at Sukagumiwang Public Health Center. This research was conducted in 2017 with research subjects being parents of toddlers. The sampling technique is total sampling. This research uses concurrent embedded design. Interviews conducted on parents who have a fat toddler. The questionnaires were distributed to the case and control group of 36 people.The results of research states that socioeconomic status and social capital are not related to the incidence of obesity.Toddlers with obesity have diverse backgrounds.Negative social support and stigma received by toddlers with obesity resulted in psychological impact and less toddler interactions.Toddlers with obesity feel different from other toddlers. Diet by consuming sweetened condensed milk and packaged sweet drinks every day triggers overweight.